Translation and canonization of texts With special reference to the latin Renditions of aratus’ phaenomena (Argos, 2015)
The present article discusses how linguistic and stylistic considerations are significant and even critical to the acceptance, survival, and ultimately to the canonical status of literary works. The choice of subject, style and the translation process are factors which influenced the status and fate of many literary compositions. We use this criterion to examine the case of Aratus’ Phaenomena, one of the most successful poems of antiquity. Our paper focuses on how the survival and popularity of Aratus’ poem were affected by its being translated into Latin by Cicero, Germanicus and Avienus.
Keywords: canonization; translation; commentary; Aratus; astronomy